Análise da semivariografia temporal de reflexões ondulares no cerrado mato-grossense - Cunha, Cristiano Rocha da (2016)
In recent years much has been researched on the environmental nature of changes that the planet is experiencing, among these changes there are the temperature that the soil cover features. It is noteworthy that the energy from the sun contributes to raising the temperature of a surface must first of all be cleared in two cases: the radiation balance and energy balance. The first is correlated with the surface albedo, an energy percentage indicator index, which is returned to the space; the second, with the partitioning of the surface energy balance. Understanding the pattern of reflection of these waves over time is critical to predict future trends in their behavior. The reflection indices studied in this research belong to a dirty field cerrado region of cuiabana downloaded. Using the Python programming language, it was developed routines geostatistical modeling in automated time by cross-validation supported by nonparametric statistics. In order to practice test procedures developed were modeled the semivariances Global Albedo, Radiation Reflectance PAR and IV. The model adjustment used a cross-validation K-fold with 10 partitioning. The analysis demonstrated a time-dependent around 200 days for semi variance of global albedo and reflectance IR, as for the PAR radiation, this value was approximately 100 days beyond semivariográfico templates for modeling the series, so contribute to the management and operation in future work.